Impact of biochars on swell–shrinkage behavior, mechanical strength, and surface cracking of clayey soil. Issue 6 (13th October 2014) - Zong, Yutong; Chen, Danping; Lu, Shenggao
Abstract Swell–shrinkage, cracking and stickiness of expansive clayey soils usually lead to their low yield. Improvement of these poor soil physical properties is a key goal for enhancing the crop productivity of expansive clayey soils. This article presents results of a study on the impact of three biochars produced from wheat straw (SB), woodchips (WCB), and wastewater sludge (WSB) on the swell–shrinkage behavior, mechanical strength, and surface cracking of a clayey soil. The soil was treated with biochars at the rate of 0, 20, 40, and 60 g biochar kg−1 soil, respectively; and incubated for 180 d in glasshouse. Application of biochars decreased significantly (p < 0.01) the coefficient of linear extensibility (COLE) of the soil, the effect of SB being most prominent. The tensile strength (TS) of the clayey soil was originally 937 kPa, which decreased to 458 kPa, 495 kPa and 659 kPa for 6% SB‐, WCB‐, and WSB‐amended soils, respectively. Shear strength tests indicated that biochars significantly reduced cohesion (c) and increased internal friction angle (θ). Biochar significantly reduced the formation of soil surface cracks, surface area, and length of the cracks. The surface area density of cracks in the 6% biochar‐amended soils decreased by 14% for SB, 17% for WCB, and 19% for WSB, respectively, compared with control. The results suggest that biochar can be used as a soil amendment for improving the poor physical properties of the clayey soil, particularly in terms of reduction in swell–shrinkage, tensile strength and surface area density of cracking.